In the first quarter of the 19 century in the emirates is bukhara and international relations - Sharofov Sardor Shuxrat oʻgʻli (Zien Journals, 2022)
This article in the first quarter of the 19th century in Bukhara emirates foreign policy, diplomatic relations with foreign countries, taking the word referred to stuck. In this article foreign policy in the period mainly emirates speech amir in bukhara, central asia and russia in the first quarter of the xix century to the competition between the uk, lit.
Keywords: Heydar Amir Mir Izzatulloh; Adilnosir Subhonqulov the delegation of the ministry Ost-India; Muhammad KHofiz Fozilxon memorial; the sultan Mahmud II